Arthroscopic Repair of Full-Thickness Rotator Cuff Tears With and Without Acromioplasty: Randomized Prospective Trial With 2-Year Follow-up. (June 2014) - Abrams, Geoffrey D.; Gupta, Anil K.; Hussey, Kristen E.; Tetteh, Elizabeth S.; Karas, Vasili; Bach, Bernard R.; Cole, Brian J.; Romeo, Anthony A.; Verma, Nikhil N.
Background: Acromioplasty is commonly performed during arthroscopic rotator cuff repair, but its effect on short-term outcomes is debated. Purpose: To report the short-term clinical outcomes of patients undergoing arthroscopic repair of full-thickness rotator cuff tears with and without acromioplasty. Study Design: Randomized controlled trial; Level of evidence, 2. Methods: Patients undergoing arthroscopic repair of full-thickness rotator cuff tears were randomized into acromioplasty or nonacromioplasty groups. The Simple Shoulder Test (SST), American Shoulder and Elbow Surgeons (ASES) score, Constant score, University of California–Los Angeles (UCLA) score, and Short Form–12 (SF-12) health assessment were collected along with physical examination including range of motion and dynamometer strength testing. Intraoperative data including tear size, repair configuration, and concomitant procedures were recorded. Follow-up examination was performed at regular intervals up to 2 years. Preoperative imaging was reviewed to classify the acromial morphologic type, acromial angle, and lateral acromial angulation. Results: A total of 114 patients were initially enrolled in the study, and 95 (83%; 43 nonacromioplasty, 52 acromioplasty) were available for a minimum 2-year follow-up. There were no significant differences in baseline characteristics, including number of tendons torn, repair configuration, concomitant procedures, and acromion type and angles. Within groups, there was a significant ( P < .001) improvement in all functional outcome scores from preoperatively to all follow-up time points, including 2 years, for the nonacromioplasty and acromioplasty groups (ASES score: 55.1-91.5, 48.8-89.0; Constant score: 48.3-75.0, 51.9-78.7, respectively). There were no significant differences in functional outcomes between nonacromioplasty and acromioplasty groups or between subjects with different acromial features at any time point. Conclusion: The results of this study demonstrate no difference in clinical outcomes after rotator cuff repair with or without acromioplasty at 2 years postoperatively.